PEMANFAATAN ABU KERTAS DAN SERBUK CANGKANG LOKAN PADA CAMPURAN BETON NORMAL DENGAN MENGGUNAKAN SIKACIM CONCRETE ADDITIVE - Mulyati Mulyati; Wiki Yulandi (Ensiklopedia of Journal, 2021)
This research uses paper ash, lokan shell powder, and sikacim concrete additivefor normal concrete mix. Paper ash is used as a cement additive, while lokan shell powder is used as a partial substitute for sand. To overcome the lack of water in the concrete mixture, Sikacim concrete additive is used. The purpose of this study was to determine the compressive strength of concrete resulting from the use of paper ash as an additive and lokan shell powder as a substitute for sand by adding sikacim concrete additive.The test object used a cube mold of 15 cm x 15 cm x 15 cm with a concrete compressive strength of K-250 design at the age of 28 days of testing. Variations of the specimens used paper ash 0.25% by weight of cement, and lokan shell powder 0%, 10%, 20%, 30% by weight of sand, and 0.7% additive from the volume of water. Based on the results of the compressive strength test of concrete, the compressive strength of concrete is obtained, for normal concrete it is 276.6 kg/cm2, from the use of 0.25% paper ash, 0% lokan shell and 0.7% additive of 362.6 kg/cm2, from the use of 0.25% paper ash, 10% lokan shell and 0.7% additive of 365.3 kg/cm2, from the use of 0.25% paper ash, 20% lokan shell and 0.7% additive of 300.53 kg /cm2, from the use of 0.25% paper ash, 30% lokan shell and 0.7% additive of 250.16 kg/cm2.